MARKETING STRATEGIES FOR INCREASING SALES OF SASA COCONUT MILK PRODUCTS (A CASE STUDY AT PT. TUMBAKMAS NIAGA SAKTI, RANGKAS BRANCH) - Sutrimono; Beni Sofa Romdoni; Andy Sahat Sigalingging (Gema Kampus IISIP YAPIS Biak, 2026)
Increasingly fierce business competition requires companies to implement effective marketing strategies to boost product sales. This study aims to analyze marketing strategies in increasing sales of Santan Sasa products at PT. Tumbakmas Niaga Sakti, Rangkas Branch. The marketing strategy analysis was conducted using the Segmenting, Targeting, Positioning (STP) approach as well as the marketing mix, which consists of product, price, promotion, and place. This study employs a qualitative method with a descriptive approach. Data were collected through observation, interviews, and documentation. The results indicate that the marketing strategies implemented by the company are quite effective in increasing consumer purchasing interest and sales revenue. The implementation of promotional activities such as price discounts, direct gifts, and promotional events at traditional markets has a positive impact on sales growth